Immature stages of Neotropical Enochrus (Coleoptera: Hydrophilidae): E. (Methydrus) lampros Knisch, 1924 and E. (Hugoscottia) tremolerasi Knisch, 1922 - Archangelsky, Miguel (2002)
The preimaginal stages of the Neotropical species E. (M.) lampros Knisch, and Enochrus (H.) tremolerasi Knisch, are described and illustrated for the first time. They are compared to the immatures of the Neotropical species E. (M.) vulgaris (Steinheil) and E. (Hugoscottia) scutellaris (Bruch), the Nearctic E. (M.) fimbriatus (Melsheimer) and E. (M.) pygmaeus nebulosus Say, and the Australian E. (M.) maculiceps (MacLeay). Bionomical notes on the two species are included.